(untitled) (World of finance, 2023)
Introduction. In the conditions of political instability, unfavorable economic situation due to the pandemic and uncertainty due to the Russian-Ukrainian war, the relevance of various types of insurance is increasing. Therefore, insurers are faced with the problems of minimizing financial risks, balancing between a sufficient level of profitability and public trust in insurance products. Under such circumstances, insurance companies are forced to make timely management decisions that must ensure financial stability while preventing the loss of competitive advantages in the insurance market. The purpose of the article is to determine the definitive characteristics of the financial stability of insurance companies and, taking into account the performance indicators of insurers on the insurance market, carry out their analytical evaluation. Results. The definition of “financial stability” of an insurance company was studied, its essential characteristics were singled out, which made it possible to distinguish between the concepts of “financial stability“ and “financial reliability” of an insurer. Factors influencing the financial stability of insurance companies are determined, based on the results of an empirical assessment of the performance indicators of insurers in modern conditions. It was established that the optimally formed amount of own capital is not an indisputable criterion of the insurer’s financial reliability. The necessity of balancing all types of activities of insurers on the insurance market based on domestic realities is substantiated. Perspectives. The subject of further scientific research is the study of the impact of endogenous and exogenous factors on the financial stability of insurance companies, which can be assessed using the proposed indicators.